Stability Analysis of an Assembly Process Using Simulation - Rónai, László; Szabó, Tamás (Acta Technica Jaurinensis, 2020)
This paper deals with an assembly process of batteries with cell holder. The operation involves snap-fitting phenomenon, which is a mechanical stability problem. The structure of the cell holder is modelled with 2D flexible beam elements assuming large displacements. The stability of the equilibrium is investigated taking into consideration non-frictional and Coulomb frictional contacts. The goal of the analysis to determine the boundary point of the feed-motion from which the battery snaps-in to the final assembled position autonomously. The effect of the velocity of the battery feed-motion is also considered with energy approach.